Geotourism Perception by Ouro Preto (Brazil) World Heritage Site Managers - Fonseca , Ricardo; Moutinho, Nathália Machado; Castro, Paulo de Tarso Amorim (Anais Brasileiros de Estudos Turísticos, 2022)
The historic city of Ouro Preto was the first Brazilian heritage site recognized by Unesco, especially for cultural criteria. The city and its surroundings have a rich cultural and natural heritage, which can be further explored by geotourism, interpreting abiotic aspects, such as relief and rocks. In this sense, the objective of the research was to aim to understand the perception of geotourism by managers of the Ouro Preto heritage. The methodology took place in office and field stages. In the first one, there was a bibliographic and digital review and documental research, elaboration of a data collection instrument (structured qualitative and quantitative forms). In the second, remote interview application by Google Meet to a focus group of heritage managers in Ouro Preto. The results found demonstrate: that the offer of commercialized tourist attractions has geotourism potential; and that geotourism is still a poorly understood concept, with great emphasis on cultural heritage (and cultural tourism), and when natural heritage is associated with ecotourism and natural protected areas. It is concluded that there is a need for greater training in geotourism for the social actors responsible for heritage decision-making.